2016
DOI: 10.1080/21645515.2016.1223001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prophylactic ibuprofen and paracetamol administration on the immunogenicity and reactogenicity of the 10-valent pneumococcal non-typeableHaemophilus influenzaeprotein D conjugated vaccine (PHiD-CV) co-administered with DTPa-combined vaccines in children: An open-label, randomized, controlled, non-inferiority trial

Abstract: Prophylactic paracetamol administration impacts vaccine immune response; this study (www.clinicaltrials.gov: NCT01235949) is the first to assess PHiD-CV immunogenicity following prophylactic ibuprofen administration. In this phase IV, multicenter, open-label, randomized, controlled, non-inferiority study in Romania (November 2010–December 2012), healthy infants were randomized 3:3:3:1:1:1 to prophylactically receive immediate, delayed or no ibuprofen (IIBU, DIBU, NIBU) or paracetamol (IPARA, DPARA, NPARA) afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Lower impact after dose 2. 105, 106, 112, 113 ↓ Fever↓ Swelling↓ PainAdministered therapeutically↓ FeverNo impact.↓ Pain Oral ibuprofen b Administered prophylactically at the time of vaccination and within the following 24 hLimited impact↓ pertussis toxin, tetanus. No impact after the second dose. 103, 112 Administered therapeutically↓ FeverNo impact.↓ Pain a One publication in older adults (mean ages 73–75 years). Results showed no impact on antibody levels and limited impact on symptoms b No data in older adults…”
Section: Symptom Managementmentioning
confidence: 99%
“…Lower impact after dose 2. 105, 106, 112, 113 ↓ Fever↓ Swelling↓ PainAdministered therapeutically↓ FeverNo impact.↓ Pain Oral ibuprofen b Administered prophylactically at the time of vaccination and within the following 24 hLimited impact↓ pertussis toxin, tetanus. No impact after the second dose. 103, 112 Administered therapeutically↓ FeverNo impact.↓ Pain a One publication in older adults (mean ages 73–75 years). Results showed no impact on antibody levels and limited impact on symptoms b No data in older adults…”
Section: Symptom Managementmentioning
confidence: 99%
“…For PCV10, a decreased immune response was noted in Prymula et al, and Falup et al [ 21 , 23 ]. Particularly, in Prymula et al, significantly lower antibody titers for all ten vaccine serotypes were observed one month after the primary vaccination in the group of children who received paracetamol with vaccination (t:0 h) compared with the group that did not receive paracetamol.…”
Section: Resultsmentioning
confidence: 97%
“…OPA GMTs detected no differences. Post booster: No effect Falup et al 2017 [ 23 ] Romania, 2016, RCT, Open label, unblinded 850 PCV10 (Synflorix™, GSK) DTPa-HBV-IPV/Hib (Infanrix Hexa™, GSK) 3, 4, 5 m/12–15 m Paracetamol Syr (15 mg/kg/dose) Ibuprofen Syr (10 mg/kg/dose) 3 doses/ 6–8 h for 24 h. t:0 h or t: 4-6 h ΙgG GMCs 1 m post-primary and booster dose (sp cut off: GMCs ≥0,2 μg/ml-22F-inhibition ELISA) Post primary: % GMCs ≥0.2 μg/mL lower in IPARA and DPARA vs NPARA (highest difference for 6B serotype) GMCS for serotypes 1, 4, 5, 9 V, 14, 18C in IPARA and 1,6B in DPARA lower vs NPARA. Post booster: GMCs in IPARA-ΝPARA and the majority of participants in DPARA-IPARA lower vs NPARA-NPARA Prymula et al 2014 [ 22 ] Czech Republic, 2014, RCT, Open label, unblinded 558 PCV7 (Prevenar™, Pfizer) 4CMenB (Bexsero™, Novartis) DTaP-HBV-IPV/Hib (Infanrix Hexa GSK) 2, 3, 4 m/12 m Paracetamol Syr (10-15 mg/kg) 3 doses/ 4–6 h for 24 h. t:0 h ΙgG GMCs 1 m post-primary and booster dose (sp cut-off: GMCs ≥0.35 μg/ml non-22F ELISA) GMCs for all serotypes in PARA lower vs NPARA (no statistical significance) Prymula et al 2013 [ 17 ] Czech Republic, 2012, RCT, unblinded (Follow up of Prymula et al 2009) 443 PCV10 (Synflorix GSK) 31–44 m (2nd booster dose) Paracetamol only at primary and 1st booster dose ΙgG GMCs before and 7–10 days after 2nd booster dose (sp cut-off: GMCs ≥0,2 μg/ml-22F-inhibition ELISA) OPA GMTs Before the 2nd booster: GMCs for serotypes 1, 4, 5 in PARA lower vs NPARA (borderline statistical significance).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the preventable AEFI reports were due to the potential interaction between the components of the vaccines or between the vaccines and concomitant medications administered to the patients. Previous studies have documented poor immunologic response to conjugated Pneumococcus vaccine following acetaminophen administration (Prymula et al, 2009; Falup-Pecurariu et al, 2017; Wysocki et al, 2017). We also reported one case of interaction between varicella, live-attenuated vaccine, and the glucocorticoid betamethasone, which may result in an inadequate immunological response to the live vaccine (Infectious Diseases and Immunization Committee, Canadian Paediatric Society, 2000; Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%